Enhancing Moral and Spiritual Development in Early Childhood Education Through the Ponakawan Philosophy - Mubin, Nurul; Haryanto, Sri; Syam, Robingun Suyud The; Hita, I Putu Agus Dharma (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the integration of Ponakawan philosophy into early childhood education curricula. The research addresses a critical gap in the literature, where traditional Javanese philosophical concepts have not been systematically examined for their pedagogical value in modern educational settings. By analyzing 36 sources of literature using a qualitative interpretive approach, this study provides a philosophical and educational perspective on how Ponakawan values can contribute to character development in young learners. The methodology involves a systematic literature review combined with a thematic analysis to synthesize key philosophical principles and their potential applications in early childhood education. The findings highlight that Ponakawan philosophy, emphasizing wisdom, humility, and social harmony, aligns with contemporary educational frameworks that promote holistic child development. However, the study also identifies challenges in adapting traditional wisdom into structured curricula. This research contributes to the field by bridging indigenous knowledge with contemporary pedagogy, offering practical insights for curriculum developers and educators. The study's implications suggest that integrating Ponakawan philosophy into PAUD curricula can enrich children's moral and social development. Future research should explore empirical applications and the effectiveness of this approach in diverse educational contexts.